Conceptualising violence in close relationships: discrepancies between police conceptions and the letter of the law in Finland - Fagerlund, Monica (European journal on criminal policy and research, 2022)
The focus in this Finland-based study is on violence in close relationships—a term that partly overlaps with the more commonly used ‘domestic violence’, ‘family violence’ and ‘intimate partner violence’. We demonstrate how police officers’ conceptualisations of such violence differ from how it is defined in relevant legal documents. The data consists of the Government Bill and legal text on the subject issued as part of a legal reform enacted in 2010, and of a qualitative sample of freelist responses from 79 police officers. We examined both sets of data using theory-driven directed content analysis and deriving from prevailing theoretical frameworks reflecting the family- and gender-based perspectives on violence. The results expose the predominance of a narrow definition of ‘family’ in police understandings of close relationships, but also a notably broad spectrum of conceptualisations of both physical and non-physical forms of violence. In contrast, the legal definition of a close relationship is broader and encompasses multiple types of relationships, whereas forms of violence are more strictly defined. These findings could explain some of the discrepancies between legal policies on violence in close relationships and police responses to it.